Situações-problemas aplicadas na aprendizagem de equações e sistemas de equações do primeiro grau com duas variáveis - Tolentino, Gilmar (2013)
The development of this work aims to aims to show the importance of the application of problem situations for the learning of equations and systems of first degree equations with two variables by students of the 8th grade level in paper and pencil environment and observation of two-pan balance. The proposal is to show the application of solving problem which involves first-degree equations with one unknown and systems of first-degree equation with two unknowns, in order to encourage the students to think, state the solution of the problem, try to overcome the learning difficulties, facing challenges which requires a great effort and dedication and find out by themselves the best strategy which must be used in order to solve the problem and, after this, compare and present the algorithms defined for the solution of these concepts. It is also presented the solution of these problems using the twopan balance method, the addition and substitution method, as well as the method of solving equations and equation systems with two unknowns.